Co-regulation of the DAF-16 target gene, cyp-35B1/dod-13, by HSF-1 in C. elegans dauer larvae and daf-2 insulin pathway mutants. - Wendy B Iser; Mark A Wilson; William H Wood; Kevin Becker; Catherine A Wolkow (PLoS ONE)
Insulin/IGF-I-like signaling (IIS) has both cell autonomous and non-autonomous functions. In some cases, targets through which IIS regulates cell-autonomous functions, such as cell growth and metabolism, have been identified. In contrast, targets for many non-autonomous IIS functions, such as C. elegans dauer morphogenesis, remain elusive. Here, we report the use of genomic and genetic approaches to identify potential non-autonomous targets of C. elegans IIS. First, we used transcriptional microarrays to identify target genes regulated non-autonomously by IIS in the intestine or in neurons. C. elegans IIS controls expression of a number of stress response genes, which were differentially regulated by tissue-restricted IIS. In particular, expression of sod-3, a MnSOD enzyme, was not regulated by tissue-restricted IIS on the microarrays, while expression of hsp-16 genes was rescued back to wildtype by tissue restricted IIS. One IIS target regulated non-autonomously by age-1 was cyp-35B1/dod-13, encoding a cytochrome P450. Genetic analysis of the cyp-35B1 promoter showed both DAF-16 and HSF-1 are direct regulators. Based on these findings, we propose that hsf-1 may participate in the pathways mediating non-autonomous activities of age-1 in C. elegans.